2002
DOI: 10.1038/modpathol.3880536
|View full text |Cite
|
Sign up to set email alerts
|

Availability of CD10 Immunohistochemistry as a Marker of Breast Myoepithelial Cells on Paraffin Sections

Abstract: CD10, also called common acute lymphoblastic leukemia antigen (CALLA), was recently found to be expressed in nonhematopoietic tissues. Although CD10 was also identified in human breast myoepithelial cells, its availability of immunohistochemistry on paraffin sections has not been examined so far. In the present study, we demonstrated CD10 immunohistochemically on paraffin sections of both normal and pathological breast tissues, comparing its staining patterns to those of smooth muscle actin (SMA), which is now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
99
2
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 18 publications
5
99
2
3
Order By: Relevance
“…The number of cases staining for CD10 and smooth muscle actin was more limited, but these are the most likely cases with more definite myoepithelial differentiation. Neither CD10 7,8 nor smooth muscle actin 9,10 has been shown previously, or in this study, to stain luminal epithelial cells. If the cases positive with these two antibodies are considered together, this would mean that 22 out of the 77 ER-negative tumours (29%) showed strong evidence of myoepithelial differentiation, and 10 of these 22 were also positive for S100.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The number of cases staining for CD10 and smooth muscle actin was more limited, but these are the most likely cases with more definite myoepithelial differentiation. Neither CD10 7,8 nor smooth muscle actin 9,10 has been shown previously, or in this study, to stain luminal epithelial cells. If the cases positive with these two antibodies are considered together, this would mean that 22 out of the 77 ER-negative tumours (29%) showed strong evidence of myoepithelial differentiation, and 10 of these 22 were also positive for S100.…”
Section: Discussioncontrasting
confidence: 99%
“…This dichotomy of expression was also noted, to some extent, in stromal myofibroblasts, which tended to be more commonly and extensively stained with smooth muscle actin rather than CD10, although positive staining with the latter was noted in several cases in this as well as in other studies. 8,37 In this respect, recent studies have suggested the existence of more than one type of myofibroblasts in breast lesions, which vary in their expression of smooth muscle actin and CD34. 38 It has to be added here, that it would be interesting to compare the staining results of the recently introduced nuclear myoepithelial cell marker p63 39 with the more established cytoplasmic markers for these cells in a future study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the expression patterns of CK7, CK8, CK14, CK19, a-smooth muscle actin (aSMA), caldesmon and calponin have been reported already, [2][3][4][5][6][7] there are only a few reports, or none, describing the expression of p63, 4,8 maspin, 14-3-3s, CD10 9 and CD44v6 10 in salivary gland tumors. Briefly, the putative functions of these molecules are summarized as follows.…”
mentioning
confidence: 99%